Insights into the control of RAD51 nucleoprotein filament dynamics from single-molecule studies. (December 2021) - Morati, Florian; Modesti, Mauro
Abstract : Genomic integrity depends on the RecA/RAD51 protein family. Discovered over five decades ago with the founder bacterial RecA protein, eukaryotic RAD51 is an ATP-dependent DNA strand transferase implicated in DNA double-strand break and single-strand gap repair, and in dealing with stressed DNA replication forks. RAD51 assembles as a nucleoprotein filament around single-stranded DNA to promote homology recognition in a duplex DNA and subsequent strand exchange. While the intrinsic dynamics of the RAD51 nucleoprotein filament has been extensively studied, a plethora of accessory factors control its dynamics. Understanding how modulators control filament dynamics is at the heart of current research efforts. Here, we describe recent advances in RAD51 control mechanisms obtained specifically using fluorescence-based single-molecule techniques.